A case of 49,XXXYY followed-up from infancy to adulthood with review of literature - Junko Kanno; Akinobu Miura; Sayaka Kawashima; Hirohito Shima; Dai Suzuki; Miki Kamimura; Ikuma Fujiwara; Masayuki Kamimura; Mitsugu Uematsu; Masataka Kudo; Atsuo Kikuchi (Endocrine Journal)
49,XXXYY is an extremely rare sex chromosomal aneuploidy (SCA), with only seven cases reported worldwide to date. Among these cases, only three have been documented into adulthood. Moreover, no cases of 49,XXXYY have been reported in Japan. This SCA has been identified in two scenarios: in vitro fertilization and abortion. Similar to 47,XXY, this aneuploidy is a type of Klinefelter syndrome. Aneuploidy of the X chromosome can lead to various progressive complications due to excess X chromosomes. Herein, we present the case of a Japanese man with 49,XXXYY. He exhibited developmental delays and external genitalia abnormalities since early infancy but was not closely monitored for these symptoms until the age of 3 years old. At that time, a chromosome test revealed his karyotype to be 49,XXXYY. Subsequent examinations were conducted due to various symptoms, including delayed motor development, intellectual disability, facial dysmorphisms, forearm deformities, hip dysplasia, cryptorchidism, micropenis, primary hypogonadism, and essential tremor. Since reaching puberty, he has undergone testosterone replacement therapy for primary hypogonadism, experiencing no complications related to androgen deficiency to date. He has maintained normal lipid and glucose metabolism, as well as bone density, for a prolonged period. There are no other reports on the long-term effects of testosterone treatment for the SCA. Appropriate testosterone replacement therapy is recommended for individuals with 49,XXXYY to prevent complications. This report will contribute to an enhanced understanding of the 49,XXXYY phenotype, aiding in the diagnosis, treatment, and genetic counseling of future cases.